Efficacy of F-18-2-fluoro-2-deoxy-D-glucose Positron Emission Tomography/Computerized Tomography for Bone Marrow Infiltration Assessment in the Initial Staging of Lymphoma - TOPTAŞ, TAYFUR (GALENOS YAYINCILIK, 2017)
Objective: Currently F-18-2-fluoro-2-deoxy-D-glucose (F-18-FDG) positron emission tomography/computerized tomography (PET/CT) is being successfully used for staging and follow-up of Hodgkin's lymphoma (HL) and non-Hodgkin's lymphoma (NHL). Various studies have demonstrated that PET/CT effectively detects bone marrow involvement (BMI) and is concordant with bone marrow biopsy (BMB) findings, thus it is deemed as a complementary method. This study was aimed to evaluate-F-18-FDG-PET/CT efficiency for detection of BMI in HL and NHL. Methods: The study included 172 lymphoma cases who were admitted to Akdeniz University Medical School Department of Nuclear Medicine for initial staging with PET/CT. Visual and semiquantitative assessments were performed for PET/CT scan findings of the cases. The maximum standard uptake (SUVmax) value was the quantitative parameter used for F-18-FDG-PET scan. In visual assessment, bone marrow metabolic activity that is greater than the liver was considered as pathologic. For semiquantitative assessment, regions of interest were drawn for SUVmax estimation, which included iliac crest in cases with diffusely increased metabolic activity and the highest activity area in cases with focal involvement. BMB was considered as the reference test. Results: On visual assessment of all the cases, PET/CT was found to yield 31% sensitivity and 85% specificity rate for detection of BMI. On visual assessment of HL cases, sensitivity rate was determined as 80%, and specificity as 78%, while in NHL cases the corresponding values were 24% and 90%, respectively. On semiquantitative assessment of HL cases, considering SUVmax=4, sensitivity was found as 80% and specificity as 68%. In NHL patients, considering SUVmax=3.2, sensitivity rate was detected as 65% and specificity as 58%. Conclusion: In this study, a moderately high concordance was observed between PET/CT and BMB findings. PET/CT appears to be a significant method for detecting BMI. Although PET/CT is not a substitute for BMB, we suggest it can be used as a guide to biopsy site and a complementary imaging technique for BMB.
Keywords: Hodgkin's lymphoma; non-Hodgkin's lymphoma; positron emission tomography/computerized tomography; bone marrow biopsy; NON-HODGKINS-LYMPHOMA; F-18-FDG PET/CT; AGGRESSIVE LYMPHOMA; MALIGNANT-LYMPHOMA; CELL LYMPHOMA; FDG-PET/CT; INVOLVEMENT; BIOPSY; DISEASE; MANAGEMENT